ANALYSIS OF THE CURRENT STATE AND PROSPECTS OF DEVELOPMENT OF SIMULATION - Olga I. Babina (Статистика и экономика, 2016)
The paper is devoted to the comprehensive analysis of a current state and prospects of development of world science in the field of simulation, features of development of this direction in Russia. Prospects of future development of simulation are considered. Systematization the resources internet devoted to simulation in Russia and abroad is carried out.